Analysis of Legal Authority of Notary Make Deed Contract in Islamic Banking - Muhammad Haidar Fitri; Achmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Act No. 30 of 2004 concerning Notary (UUJN) as amended by Act No. 2 of 2014 and Act No. 21 of 2008 of Islamic Banking (UUPS) has give authority to make attributive to the notary deed in Islamic banking contract. Notary in question is the one who meets the criteria of Article 3 UUJN and has been appointed by the Minister of Justice and Human Rights as a notary. Deed of Islamic banking contract has the power as valid evidence, when manufacture has to comply with the following requirements; as a mechanism of certificates in accordance with the matters set out in UUJN and UUPS, while in the content or deed bodies are in accordance with Law Compilation of Islamic Economics (KHES).Keywords: Legal Authority; Notary; Deed Contract; Islamic Banking.